2016
DOI: 10.1007/s10863-016-9666-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium supplementation on electrophysiological remodeling of cardiac myocytes in L-NAME induced hypertensive rats

Abstract: Hypertension is one of the major risk factors of cardiac hypertrophy and magnesium deficiency is suggested to be a contributing factor in the progression of this complication. In this study, we aimed to investigate the relationship between intracellular free Mg(2+) levels and electrophysiological changes developed in the myocardium of L-NAME induced hypertensive rats. Hypertension was induced by administration of 40 mg/kg of L-NAME for 6 weeks, while magnesium treated rats fed with a diet supplemented with 1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Magnesium (Mg) is a mineral critical for normal cardiac function and provides an antiarrhythmic action [29, 30]. It also reduces hypertension and provides antioxidant and anti-hyperlipidemic effects [31, 32]. In humans, inadequate Mg is correlated with heart failure and increased risk for various cardiovascular disorders [30, 3335].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) is a mineral critical for normal cardiac function and provides an antiarrhythmic action [29, 30]. It also reduces hypertension and provides antioxidant and anti-hyperlipidemic effects [31, 32]. In humans, inadequate Mg is correlated with heart failure and increased risk for various cardiovascular disorders [30, 3335].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension can cause damage to various target organs in the body (including heart, brain and kidneys) (4). Long-term and sustained hypertension can lead to increased cardiac load, easily resulting in myocardial morphological and structural changes such as cardiac hypertrophy, interstitial fibrosis, ventricular dilatation and cardiomyocyte apoptosis (5). A study has demonstrated that cardiomyocyte apoptosis, as a cytological basis and initiator of left ventricular remodeling of hypertension, plays a regulatory role in the whole ventricular remodeling (6).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this study was showed that lower level of magnesium was an independently predictor of MACCE, especially cardiovascular mortality; and serum cTnT concentration was higher in LM group compared with HM group with statistical signi cance. Besides the in uence of vascular damage, in ammation and protein-energy malnutrition by relative magnesium de ciency, magnesium insu ciency was reported to be related to the myocardial remodeling and electrophysiology abnormality [32][33][34].…”
Section: Discussionmentioning
confidence: 99%